The role of cytochrome P4502E1 in ethanol mediated diseases: a narrative update - Zakhari, Samir; Neuman, Manuela G.; Seitz, Helmut K. (Alcohol and alcoholism, 2025)
Cytochrome P450 (CYPs) superfamily of enzymes metabolize thousands of endogenous and exogenous substrates including ethanol. Results: Cytochrome P4502E1 (CYP2E1) is involved in ethanol metabolism as part of the so-called microsomal ethanol metabolizing system, in the metabolism of fatty acids and some drugs such as acetaminophen and isoniazid, and in the activation of a variety of procarcinogens (PCs). Chronic ethanol consumption induces CYP2E1 which may result in an enhanced metabolism of these drugs to their toxic intermediates, and in the generation of carcinogens. In addition, ethanol oxidation increases and is associated with the generation of reactive oxygen species (ROS). This oxidative stress is an important driver for the development of alcohol-associated liver disease (AALD) and alcohol-mediated cancer (AMC). ROS may bind directly to proteins and to DNA. ROS may also lead to lipid peroxidation (LPO) with the generation of LPO products. These LPO products may bind to DNA forming etheno-DNA adducts. Cell culture studies as well as animal experiments have shown that CYP2E1 knock-out animals or the inhibition of CYP2E1 by chemicals results in a significant improvement of liver histology. CYP2E1 is also involved in pathogenesis of hepatic steatosis and fibrosis. More recent studies in patients with AALD have demonstrated an improvement of serum transaminase activities when CYP2E1 was inhibited by clomethiazole. In addition to its role in the generation of ROS, CYP2E1 also enhances the activation of PCs and decreases the level of retinol and retinoic acid in the liver. Conclusion: Inhibition of CYP2E1 may improve AALD and may inhibit AMC. The activity of cytochrome P450 (CYP2E1) as part of the microsomal ethanol oxidizing system increases following chronic alcohol consumption which results in oxidative stress contributing to alcohol-associated liver disease (AALD) and cancer. CYP2E1 also toxify some drugs and PCs, and decreases retinoic acid. Inhibition of CYP2E1 improves alcoholic liver diseases (ALD) even in humans.
Gesehen am 03.12.2025